Methicillin Resistant Staphylococcus aureus Contamination of Hands and Mobile Phones of Health Care Workers in a Health Care Setting: A Silent Threat - Sharma, B.K.; Regmi, S.M.; Sharma, K.; Reddy, K.R.; Adhikari, S. (Journal of Gandaki Medical College-Nepal, 2019)
Background: The extensive use of mobile phones in the hospital among health care workers (HCWs) can lead to infectious agents being transferred from one patient to another and thus serve as a vehicle in the transmission of nosocomial pathogens.Objectives: This study aimed to investigate the prevalence of Methicillin Resistant Staphylococcus auerus (MRSA) contamination of mobile phones and hands of HCWs in Gandaki Medical College and Teaching Hospital.Methods: The present study was hospital and laboratory based cross-sectional study, carried out from April, 2017 to December, 2017. A total of 100 mobile phone swab and 100 hand swab samples of HCWs were collected and cultured directly on MacConkey agar, blood agar, and mannitol salt agar after 24 hrs of enrichment. All the isolated organisms including MRSA were identified using standard microbiological techniques and subjected to antibiotic susceptibility testing using disc diffusion technique.Results: Among the Gram positive isolates, frequency distribution from mobile phones showed the highest prevalence of coagulase negative Staphylococci (CONS) (34.69%), followed by Staphylococcus aureus (20.41%), Bacillus spp (15.31%), Micrococci spp (11.23%), however considerable number of Diptheroides (8.16%), Enterococci (6.12%) and Streptococcus pneumoniae (4.08%). Siimilarly from hand swabs CONS (39.62%), followed by S. aureus (26.42%), Bacillus spp (10.38%), Micrococci (11.32%), Enterococci (6.60%) and Diptheroids (5.66%) were isolated. The frequency of MRSA was 20%, 25% among mobile phones and hands of HCWs respectively. Drugs like Vancomycin, Amikacin, Clindamycin and Gentamycin were found quite effective against S. aureus in the present study and would be better options for the management of such infections.Conclusions: Mobile phones and hands of HCWs were the potential source of nosocomial infections including multidrug-resistant pathogens like methicillin-resistant S. aureus.